2018
DOI: 10.1097/anc.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Nurse-Guided Variables and Plasma Oxytocin Trajectories in Premature Infants During Initial Hospitalization

Abstract: Replication with larger sample sizes and randomized controlled trial designs is needed to test effects of specific nursing interventions on infant OT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…Therefore, when infants experience reducedstress states, they are able to better engage with their caregivers to facilitate bonding and are better able to safely feed, and their gastrointestinal tracts function to support digestion, restoration, and growth. The release of oxytocin not only has these direct positive benefits but also acts to block activation of the HPA axis (Gimpl & Fahrenholz, 2001), resulting in protection from the negative effects of stress as well (Weber, Harrison, Sinnott, Shoben, & Steward, 2018).…”
Section: Physiologic Response To Low Levels Of Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when infants experience reducedstress states, they are able to better engage with their caregivers to facilitate bonding and are better able to safely feed, and their gastrointestinal tracts function to support digestion, restoration, and growth. The release of oxytocin not only has these direct positive benefits but also acts to block activation of the HPA axis (Gimpl & Fahrenholz, 2001), resulting in protection from the negative effects of stress as well (Weber, Harrison, Sinnott, Shoben, & Steward, 2018).…”
Section: Physiologic Response To Low Levels Of Stressmentioning
confidence: 99%
“…Despite the evidence supporting SSC, data suggest that infants in the United States receive less than 1 hour of SSC per day and that this varies considerably, with some infants going weeks without any SSC (Reynolds et al, 2013;Weber, Harrison, Sinnott, et al, 2018). In multiple studies, researchers explored the facilitators and barriers to implementation of SSC in the NICU, and the results are fairly consistent across studies.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…Of these 19 studies, 10 (52.6%) evaluated only infants, 21-30 2 (10.5%) evaluated only parents, 31,32 and 7 (36.9%) evaluated both infants and parents. [33][34][35][36][37][38][39] For the purposes of this review, the findings from the infant (see Supplementary Table 1, available at: http://links.lww.com/ANC/A93) [21][22][23][24][25][26][27][28][29][30][33][34][35][36][37][38][39] and parent (see Supplementary Table 2, available at: http:// links.lww.com/ANC/A94) [31][32][33][34][35][36][37][38][39] studies are presented separately. Standardized criteria were developed to review the 2 groups of studies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The Italian Society of Neonatology guidelines endorsed by the Union of European Neonatal and Perinatal Societies (UENPS) suggest that rooming-in of mother and newborn is workable if a mother is SARS-CoV-2 positive or is a person under investigation (PUI), or is asymptomatic or has minimal symptoms at delivery, but with strict infection control measures 63 . Ample research-based evidence has concluded that early maternal-newborn bonding positively impacts the growth and development in term and pre-term neonates 64 , 65 . Early separation may negatively affect bonding, breast milk production and mental health of the mother during the hospital stay and after discharge with uncertain short- and long-term implications.…”
Section: Introductionmentioning
confidence: 99%